MONITORING TURNAROUND TIME USING AN AVERAGE CONTROL CHART IN THE LABORATORY - Kao, Shih-Chou (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
The long turnaround time (TAT) will prolong the waiting time of patient, increase hospital costs and decrease service satisfaction. None of the studies on control charts and medical care have applied control charts to monitor TAT and proposed a probability function for the distribution of the mean. This study proposed a general formula for the probability function of the distribution of the mean. The control limits of the average chart were determined according to the type I risks (α) and the standardized Weibull, lognormal and Burr distributions. Furthermore, compared to control charts that use α=0.0027, weighted variance (WV), skewed correction (SC) and traditional Shewhart control charts, the proposed control chart is superior to other control chart, in terms of the αs for a skewed process. An example of the TAT of laboratory for the medical center presented to illustrate these findings.